دور الإدارة النوعية للموارد البشرية في تعزيز كفاءة أداء المصارف الخاصة السورية: دراسة ميدانية على فروع المصارف الخاصة العاملة في مدينة دمشق - الشريف، بتول محمد (جامعة البعث, 2021)
تهدف هذه الدراسة إلى بيان أثر الإدارة النوعية للموارد البشرية بمكوناتها (التأهيل المعرفي، الخبرات المتعلقة بالعمل، المهارات، معنويات العاملين) على أداء المصارف الخاصة في سورية. ولتحقيق أهداف الدراسة قام الباحث بتصميم استبانة شملت (25) فقرة لجمع المعلومات الأولية من عينة الدراسة المكونة من (50) مفردة. وفي ضوء ذلك جرى جمع وتحليل البيانات واختبار الفرضيات. وبعد إجراء عملية التحليل لبيانات الدراسة وفرضياتها توصلت الدراسة إلى وجود أثر ذو دلالة إحصائية لعناصر الإدارة النوعية للموارد البشرية (التأهيل المصرفي، الخبرات المتعلقة بالعمل، المهارات، معنويات العاملين) على أداء المصارف الخاصة السورية (الربحية، الحصة السوقية) عند مستوى معنوية 5%. وقد أوصت الدراسة ضرورة قيام إدارات المصارف الخاصة السورية بتعزيز دور الإدارة النوعية للموارد البشرية وتطويرها بشكل مستمر. والسعي نحو خلق حالة المواءمة بين متغيرات البيئة الخارجية والداخلية وإدارة الموارد البشرية، كونها الوسيلة الأساسية في تحقيق الأداء الكفوء والفعال للبنوك. This study aims to demonstrate the impact of qualitative management of human resources with its components (cognitive qualification, work related experiences, skills, employee morale) on the performance of private banks in Syria. To achieve the objectives of the study, the researcher designed a questionnaire that included (25) items to collect primary information from the study sample consisting of (50) individuals. In light of this, data were collected and analyzed, and hypotheses were tested. After conducting the analysis process of the study data and its hypotheses, the study concluded that there is a statistically significant effect of the elements of qualitative management of human resources (bank qualification, work related experiences, skills, employee morale) on the performance of Syrian private banks (profitability, market share) at a level of morale of 5%. The study recommended the necessity for the Syrian private bank administrations to enhance the role of the qualitative management of human resources and to develop them on an ongoing basis.
Keywords: رأس المال الفكري -- إدارة الموارد البشرية -- المصارف والبنوك -- سوريا